In situ degradation of organophosphorus flame retardant on cellulosic fabric using advanced oxidation process: A study on degradation and characterization. (April 2016) - Yasin, Sohail; Behary, Nemeshwaree; Giraud, Stephane; Perwuelz, Anne
Abstract: N-methylol dimethyl phosphonopropionamide (MDPA) is one of the most effective organophosphorus flame retardants for cellulosic fabrics, used in combination with Trimethylol melamine (TMM) to obtain durable and improved flame retardant properties. While their use is responsible for severe health problems, there is a need today to study methods to eliminate or degrade the durable flame retardant products which stay on discarded flame retardant textiles. The final aim is to improve the reusability of discarded textiles and to increase their energetic yield during the incineration phase. In this work, the degradation and mineralization of the flame retardant MDPA on cellulosic fabric, was studied using an advanced oxidation process (AOP) based on Fenton reaction. The effect of varying concentrations of Fenton's reagents (H2 O2 and Fe 2+ in aqueous medium) on the degradation of the MDPA was studied. The degradation of MDPA in aqueous media was monitored by measuring chemical oxygen demand (COD) of the reaction mixture over time. The mechanical properties of the cellulosic fabric after Fenton's reaction were unaltered in both warp and weft directions. The flammability test and thermogravimetric (TGA and DTG) results confirmed the degradation of MDPA flame retardant from the fabric. Pyrolysis combustion flow calorimeter (PCFC) confirms that there is a higher heat release after Fenton's reaction degradation which makes the degraded flame retardant cotton interesting for energy production by incineration.